Bioprospecting Indigenous Marine Microalgae for Polyunsaturated Fatty Acids Under Different Media Conditions - Jain P; Minhas AK; Shukla S; Puri M; Barrow CJ; Mandal S (Frontiers Media S A, 2022)
Marine microalgae produce a number of valuable compounds that have significant roles in the pharmaceutical, biomedical, nutraceutical, and food industries. Although there are numerous microalgal germplasms available in the marine ecosystem, only a small number of strains have been recognized for their commercial potential. In this study, several indigenous microalgal strains were isolated from the coast of the Arabian Sea for exploring the presence and production of high-value compounds such as polyunsaturated fatty acids (PUFAs). PUFAs are essential fatty acids with multiple health benefits. Based on their high PUFA content, two isolated strains were identified by ITS sequencing and selected for further studies to enhance PUFAs. From molecular analysis, it was found both the strains were green microalgae: one of them was a Chlorella sp., while the other was a Planophila sp. The two isolated strains, together with a control strain known for yielding high levels of PUFAs, Nannochloropsis oculata, were grown in three different nutrient media for PUFA augmentation. The relative content of α-linolenic acid (ALA) as a percentage of total fatty acids reached a maximum of 50, 36, and 50%, respectively, in Chlorella sp., Planophila sp., and N. oculata. To the best of our knowledge, this is the first study in exploring fatty acids in Planophila sp. The obtained results showed a higher PUFA content, particularly α-linolenic acid at low nutrients in media.
Keywords: α-linolenic acid; indigenous microalgae; media stress; polyunsaturated fatty acids; growth kinetic